“Short Cut to America” – The Canadian Steamship Company and the Port of Paspébiac - Holman, Harry T. (The Northern Mariner / Le marin du nord)

(untitled) (Canadian Nautical Research Society and North American Society for Oceanic History, 2025)
In the closing years of the nineteenth century, transportation of mails, passengers, and goods across the North Atlantic was highly competitive. Although dominated by several large enterprises, there were attempts from smaller operators to enter the business. One factor that differentiated the lines serving Canadian ports from those operating from American locations was the effect of climate, with the winter closures of Montreal and Quebec owing to ice conditions. This paper examines one attempt, ultimately unsuccessful, to identify an alternative port that would provide year-round service.